Guinea Pig and Mouse Models for Genital Herpes Infection. Issue 12 (22nd December 2021) - Hook, Lauren M.; Friedman, Harvey M.; Awasthi, Sita
Abstract: This article describes procedures for two preclinical animal models for genital herpes infection. The guinea pig model shares many features of genital herpes in humans, including a natural route of inoculation, self‐limiting primary vulvovaginitis, spontaneous recurrences, symptomatic and subclinical shedding of HSV‐2, and latent infection of the associated sensory ganglia (lumbosacral dorsal root ganglia, DRG). Many humoral and cytokine responses to HSV‐2 infection in the guinea pig have been characterized; however, due to the limited availability of immunological reagents, assessments of cellular immune responses are lacking. In contrast, the mouse model has been important in assessing cellular immune responses to herpes infection. Both the mouse and guinea pig models have been extremely useful for evaluating preventative and immunotherapeutic approaches for controlling HSV infection and recurrent disease. In this article, we describe procedures for infecting guinea pigs and mice with HSV‐2, scoring subsequent genital disease, and measuring replicating virus to confirm infection. We also provide detailed protocols for dissecting and isolating DRG (the site of HSV‐2 latency), quantifying HSV‐2 genomic copies in DRG, and assessing symptomatic and subclinical shedding of HSV‐2 in the vagina. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Primary and recurrent genital herpes infection in the guinea pig model Support Protocol 1 : Blood collection via lateral saphenous vein or by cardiac puncture after euthanasia Support Protocol 2 : Dissection and isolation of dorsal root ganglia from guinea pigs Support Protocol 3 : PCR amplification and quantification of HSV‐2 genomic DNA from samples Basic Protocol 2 : Primary genital herpes infection in the mouse model Alternate Protocol : Flank infection with HSV‐2 in the mouse model Support Protocol 4 : Dissection and isolation of mouse dorsal root ganglia